Indirect Comparison of Lanadelumab and Intravenous C1-INH Using Data from the HELP and CHANGE Studies: Bayesian and Frequentist Analyses - Joan Mendivil; Mia Malmenäs; Katrin Haeussler; Matthias Hunger; Gagan Jain; Giovanna Devercelli (Adis, Springer Healthcare, 2021)
Abstract Background Hereditary angioedema (HAE) with C1-esterase inhibitor (C1-INH) deficiency is a rare disease associated with painful, potentially fatal swelling episodes affecting subcutaneous or submucosal tissues. HAE attacks recur with unpredictable severity and frequency throughout patients' lives; long-term prophylaxis is essential for some patients. In the absence of head-to-head studies, indirect treatment comparison (ITC) of long-term prophylactic agents is a valid approach to evaluate comparative efficacy. Methods We conducted an ITC using data from the placebo-controlled HELP study (assessing patients receiving lanadelumab 300 mg every 2 or 4 weeks) and the 12-week, parallel arm, crossover CHANGE study (assessing intravenous C1-INH). Outcomes of interest were attack rate ratio (ARR) and time to attack after day 0 (TTA0) and after day 70 (TTA70). Two ITC methodologies were used: a Bayesian approach using study results to update non-informative prior distributions to posterior distributions on relative treatment effects, and a frequentist approach using patient-level data from HELP and CHANGE to generate Poisson regressions (for ARR) and Cox models (for TTA0 and TT70). Results Both Bayesian and frequentist analyses suggested that lanadelumab reduced HAE attack rate by 46-73% versus intravenous C1-INH. Relative to intravenous C1-INH, risk of first attack after day 0 was comparable between intravenous C1-INH and both lanadelumab doses; risk of first attack after day 70 was reduced by 81-83% with lanadelumab 300 mg every 2 weeks, compared with C1-INH. Conclusions Findings from these two ITC methodologies support the favorable efficacy of lanadelumab in reducing the HAE attack rate and extending attack-free intervals in patients with HAE.